Managing Anesthesia for a Patient with Takayasu Illness. (5th January 2023) - Freitas, Gabriela; Guerra, João Luiz; Fornero, Cesar Henrique; Delgado, Marina
Abstract : This article intended to provide an overview of the anesthetic management for a patient with Takayasu arteritis, an uncommon and challenging disease. Despite the limited literature, it becomes more evident that there is no right answer for all patients. Considering that, it is important to take into account the severity and specific features of the underlying disease to decide the best anesthetic approach. In this context, an adequate preoperative assessment focusing on cardiovascular function becomes essential. Adequate cardiovascular monitoring is also essential in the intraoperative period. A multidisciplinary team should be involved in the perioperative period to provide the best care possible and improve patient outcomes. This case illustrates a successful hysterectomy in a patient with Takayasu arteritis, pointing out the pathophysiologic considerations and discussing the means to reduce the perioperative risk. The particularities described in this case report may help other physicians choose the best strategy when facing challenging patients similar to the one described.